Evolution of the Study on the Effect of Parenting on Prosocial Behaviours in Childhood and Adolescence: Systematic Review - Gómez Tabares, Anyerson Stiths; Correa Duque, Maria Cristina; González Cortés, Jorge Hernán (Actualidades en Psicología, 2021)
Objective. To conduct a systematic review of the evolution and documented empirical evidence on the effect of parenting on the development of prosocial behaviors in childhood and adolescence. Method. A bibliometric and citation network analysis was performed using bibliometrix and Tree of Science (ToS) tools. The bibliographic search was carried out in Scopus and Web of Science. Results. Scientific production between 2000 and 2020 increased between 10% and 13%. The studies were segmented into classic, structural, and recent. Classical studies analyzed the direct effect of parental discipline on prosocial behaviors. The structural ones analyzed the emotional factors that mediate the association between parenting and prosocial behaviors. The recent ones provide additional evidence on the mediating role of empathy and the incorporation of a crosscultural and ethnic perspective in the study of parenting styles and prosocial behaviors.